Sneak peek at cellphone future. - Boyd, J. (IEEE spectrum)
NTT DoCoMo Inc., Japan's largest mobile phone company, has successfully transmitted 2.5 Gb/s of packet data in a downlink to a vehicle moving at 20 km/hr. DoCoMo owed its success to using bandwidth more efficiently and partly to bumping up two key technologies: multiple-input, multiple-output (MIMO) and quadrature amplitude modulation (QAM). Despite the success, DoCoMo realizes that they still have to face many difficult challenges in the development phase and in commercializing the system. In addition to the sheer size of the equipment being used to carry out the recent tests, 4G systems need a new infrastructure to support it. Nevertheless, 4G has the potential to provide a rich multimedia experience, including realistic videoconferencing, interactive online gaming, and high definition video.